Overcoming Regulatory Barriers: A Narrative Review of Implementation Strategies and Cultural Challenges of Lean Six Sigma in a GMP Environment - Fhahira Alifiya; Andi Fadilla (CV. Wadah Publikasi Cendekia, 2025)
Pharmaceutical manufacturing is required to achieve operational efficiency while strictly complying with Good Manufacturing Practice (GMP) regulations. This dual demand often limits process improvement initiatives. Lean Six Sigma (LSS) provides a structured management approach that integrates efficiency improvement with regulatory compliance. This narrative review aims to analyze LSS implementation strategies in pharmaceutical manufacturing from a management and regulatory perspective. A focused literature review was conducted using major scientific databases. Due to the limited number of empirical studies conducted in highly regulated GMP environments, five relevant case studies were selected and analyzed using a narrative reflection approach. The analysis focused on managerial strategies, regulatory constraints, and organizational culture influencing LSS implementation. The results show that LSS strengthens GMP compliance by providing data-driven justification for process changes through the DMAIC framework. Lean tools, particularly Value Stream Mapping, enable managers to identify non-value-added activities that are not mandated by regulation. However, cultural resistance and risk-averse organizational behavior remain significant challenges, requiring strong leadership and employee involvement. In conclusion, Lean Six Sigma is an effective management strategy for overcoming regulatory and cultural barriers in pharmaceutical manufacturing while supporting sustainable operational excellence and product quality.